Trends of Gestational Trophoblastic Disease at a Tertiary Care Hospital - Shakya, Beemba; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The objective of this study was to determine the clinical presentation of GTD and response of GTN to single and multiple agent chemotherapy on the basis of WHO Prognostic risk scoring system. Methods: This was a cross-sectional retrospective study undertaken at Paropakar Maternity and Women’s Hospital. The medical records of 102 GTD cases were reviewed from January 25, 2015 to January 24, 2016. Data pertaining patient characteristics, histopathology types of GTD, management, prognostic risk scores, chemotherapy, follow up and remissions were retrieved and were analyzed using SPSS version 16.0. Results: Among 102 GTD cases, the most common presentation was vaginal bleeding 69(67.6%) followed by ultrasound diagnosed cases 30(29.4%). Primary management of all cases were suction evacuation, 68 completed and 12 are under follow-up. GTN was diagnosed in 14/90 (15.5%) of complete mole and 5/90 (5.5%) of partial mole. Twenty-two cases received chemotherapy for persistent gestational trophoblastic tumour(19) and invasive mole(3). Twenty cases were low risk score group and two cases under high risk group. Out of 20 low risk cases that received MTX-FA, 13/20 (65%) achieved remission. Due to low response of MTX-FA, five of them were converted to Actinomycin-D and achieved remission (100%). Two high risk cases received EMA-CO regimen and achieved 100% remission. Two low risk GTN, complete and invasive mole (underwent hysterectomy) are undergoing MTX-FA chemotherapy. Conclusions: The most common presentation of GTD was vaginal bleeding. Low risk GTN achieved 65% remission with Methotrexate-Folinic acid, ultimately achieved 100% remission with Actinomycin-D. High risk GTN achieved 100% remission with EMA-CO regimen.